2010
DOI: 10.1002/cncr.25259
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial membrane protein‐2 expression is an early predictor of endometrial cancer development

Abstract: BACKGROUND: Endometrial cancer (EC) is a common malignancy worldwide. It is often preceded by endometrial hyperplasia, whose management and risk of neoplastic progression vary. Previously, the authors have shown that the tetraspan protein epithelial membrane protein-2 (EMP2) is a prognostic indicator for EC aggressiveness and survival. Here the authors validate the expression of EMP2 in EC, and further examine whether EMP2 expression within preneoplastic lesions is an early prognostic biomarker for EC developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
0
32
1
Order By: Relevance
“…Preparation of breast cancer cell lines or tissue lysates for western blotting has been described previously (27). Cells were lysed in Laemmli buffer, and for EMP2 detection, were treated with N-glycosidase F (New England Biolabs, Beverly, MA) to remove N-link glycosylation (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of breast cancer cell lines or tissue lysates for western blotting has been described previously (27). Cells were lysed in Laemmli buffer, and for EMP2 detection, were treated with N-glycosidase F (New England Biolabs, Beverly, MA) to remove N-link glycosylation (15).…”
Section: Methodsmentioning
confidence: 99%
“…Belonging to the growth arrest specific-3 (GAS3) family of tetraspan proteins, elevated EMP2 levels have been observed in advanced ovarian and endometrial tumors (7, 8), and its expression inversely correlated with endometrial cancer patient survival (9). This effect could be recapitulated through xenograft modeling as endometrial tumors where EMP2 expression was increased showed enhanced tumor growth (10).…”
Section: Introductionmentioning
confidence: 99%
“…Due to non-neoplastic peritoneal, surface tissues were complete negative for EMP2 staining, thus EMP2 was regarded as increased expression in tumour cells in ovarian cancer 20. Moderately intense diffuse immunohistochemical stainings of tumour cell cytoplasm were identified in endometrioid adenocarcinoma, serous carcinoma, mixed endometrioid and serous carcinoma, mixed endometrioid and clear cell carcinoma 21. On the other hand, compared with undifferentiated ones, predominant expressions of EMP2 in cytoplasm and/or membrane of squamous metaplasias and non-keratinising NPCs were found in our study, suggesting that loss of EMP2 expression might change its interactions with some membrane proteins in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Briefly, 535 formalin-fixed, paraffin-embedded archival endometrial tissue samples were randomly collected from 207 patients by curettage, biopsy, or hysterectomy procedures dating from 1982 to 2002 (Department of Pathology and Laboratory Medicine, UCLA Medical Center) with institutional review board approval. Of the 207 patients, 150 had at least two specimens collected during separate procedures, for a total of 457 ‘serial’ specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear positivity for each case was expressed as a percentage and was calculated from the mean pooled value of TTF-1 expression from which there were multiple informative spots as previously described. [18] A positive case was defined as any nuclear TTF-1 expression in endometrial glandular cells present. For all results, p<0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%